2012
DOI: 10.1158/1078-0432.ccr-11-3348
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 Promotes Lung Cancer Progression and Chemoresistance by Upregulating p38 MAPK, ERK, and Cyclooxygenase-2

Abstract: Purpose: This study is aimed at investigating the role and novel molecular mechanisms of galectin-1 in lung cancer progression.Experimental Design: The role of galectin-1 in lung cancer progression was evaluated both in vitro and in vivo by short hairpin RNA (shRNA)-mediated knockdown of galectin-1 in lung adenocarcinoma cell lines. To explore novel molecular mechanisms underlying galectin-1-mediated tumor progression, we analyzed gene expression profiles and signaling pathways using reverse transcription PCR … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
112
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(123 citation statements)
references
References 44 publications
5
112
0
2
Order By: Relevance
“…Several mechanisms of chemoresistance have been described in solid cancers, that can be cell-intrinsic (23) or acquired during the course of the treatment (24). In NSCLC, it has been shown that galectin 1 expressed by tumor cells induces chemoresistance through upregulation of p38MAPK and ERK (25), and that nicotine induces STAT3 phosphorylation, leading to the serine/threonine kinase IKBKE oncogene activation, which leads to chemoresistance (26). However, to date, no biomarker is currently used to predict response to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms of chemoresistance have been described in solid cancers, that can be cell-intrinsic (23) or acquired during the course of the treatment (24). In NSCLC, it has been shown that galectin 1 expressed by tumor cells induces chemoresistance through upregulation of p38MAPK and ERK (25), and that nicotine induces STAT3 phosphorylation, leading to the serine/threonine kinase IKBKE oncogene activation, which leads to chemoresistance (26). However, to date, no biomarker is currently used to predict response to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…This is seen in TGTs that are particularly sensitive to CDDP because they are one of the few cancers in which p53 is rarely inactivated (6). Activation of p38 MAPK, a kinase involved in apoptosis induction, is also altered in CDDP-resistant lung cells (7,8). Prosurvival signals, such as PI3K-AKT or extracellular signal-regulated kinases (ERK), are overstimulated in some CDDPresistant cells, such as lung or ovarian cell lines (3).…”
Section: Introductionmentioning
confidence: 99%
“…14 Recent studies report that Gal-1 knockdown can sensitize melanoma and lung cancer cells to chemotherapy. 15,16 Previous studies have suggested that Gal-1 may serve as a potential marker for RCC. 17,18 However, the detailed molecular mechanisms connecting Gal-1 to RCC remain largely unknown.…”
mentioning
confidence: 99%